Substance-Associated Elevations in Monocyte Activation Among Methamphetamine Users with Treated HIV Infection - CARRICO, Adam W. (AIDS, 2018)
OBJECTIVE: Microbial translocation and monocyte activation predict mortality in treated HIV. We examined whether substance use independently contributes to these pathophysiologic processes. DESIGN: Cross-sectional study at baseline for a randomized controlled trial. METHODS: HIV-positive, methamphetamine-using men who have sex with men (MSM) with undetectable HIV viral load (< 40 copies/mL) were enrolled. We examined if plasma biomarkers of monocyte activation and intestinal barrier integrity were associated with the following: 1) reactive urine toxicology results (Tox+) for stimulants (i.e., methamphetamine or cocaine); and 2) substance use severity measured by the Addiction Severity Index. Multiple linear regression models adjusted for age, antiretroviral therapy regimen, CD4+ T-cell count, interleukin-6, and alcohol use severity. RESULTS: The sample of 84 virally suppressed MSM had a median CD4+ T-cell count of 645 cells/mm(3). Those who were Tox+ for stimulants displayed higher soluble CD14 (sCD14) levels (2,087 versus 1,801 ng/ml; p = .009), and this difference remained significant after adjusting for covariates (standardized Beta = 0.23; p = 0.026). Greater substance use severity was also independently associated with higher sCD14 after adjusting for covariates (standardized Beta = 0.29, p = 0.013). Being Tox+ for stimulants and substance use severity were not associated with soluble CD163 (sCD163) or intestinal fatty acid binding protein (iFABP) levels (p’s > 0.05). CONCLUSIONS: Monocyte activation is one plausible mechanism by which stimulant use may increase clinical HIV progression.